Muhammad: Prophet of Peace Amid the Clash of Empires By Juan Cole (New York: Nation Books, 2018. 336 pages.) (American Journal of Islam and Society, 2019)
Reference to violence and war often dominates contemporary discussions about the early Muslims. In Muhammad: Prophet of Peace Amid the Clash of Empires, Juan Cole balances the narrative by centering instead the role of peace and “peace thought”, notions which he argues more aptly characterize the early community. He situates this emergent movement within the geo-politics of the day. As the conflict between two major super-powers became perceived as approaching cataclysmic and apocalyptic proportions, the Prophet’s message juxtaposed the worldly violence of empire with the peace promised in the Quran. Within this vision lay a pursuit of temporal peace, represented by the Prophet’s own political career. Departing from those scholars who either reject the later Muslim historiographical traditionout of hand or adopt it wholesale, Cole insists on centering the Quran as a primary source, while applying a discerning eye towards the hadith and biographical sources that emerge in later centuries (228). Finally, by comparing the writings of the Prophet’s Christian-Byzantine contemporaries to the Quran, the author foreshadows the “violence thought” (i.e. rhetoric that justified or even encouraged aggressive warfare and conquest) that the institutionalization of power in the form of empire will soon demand of succeeding generations of Muslims.